Accuracy of visual inspection, cytology and colposcopy in the diagnosis of high-grade cervical intraepithelial neoplasia - Maykot Kuerten, Beatriz; Aparecido Kanzler, Sandro; Fedrizzi, Edison Natal (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Cervical cancer is still one of the leading causes of cancer and mortality in women, especially in low- and middle-income countries. Normally, the prevention of its occurrence is done through efficient screening and treatment programs for high-grade epithelial lesions, which are pre-malignant lesions. Cheaper diagnostic techniques ensure greater access to women, which can prevent a large number of cancer cases worldwide. Objective: The aim of the study was to evaluate the accuracy of visual inspection either with acetic acid or with Lugol’s iodine, cervical cytology and colposcopy in the diagnosis of cervical intraepithelial neoplasia 2 and 3. Methods: This is a study of diagnostic accuracy. We evaluated 115 women with high-grade squamous intraepithelial lesion confirmed by biopsy, 54 with cervical intraepithelial neoplasia 2 and 61 with cervical intraepithelial neoplasia 3, from January 2016 to December 2018 at the Lower Genital Tract Pathology and Colposcopy Service of the Hospital de Clínicas de Porto Alegre, Porto Alegre, Brazil. A comparative analysis of the visual inspection, Pap smear and colposcopy diagnostic methods was performed. Results: The average age was 33.1 years (standard deviation=9.83) for cervical intraepithelial neoplasia 2 cases and 35.2 years (standard deviation=7.97) for cervical intraepithelial neoplasia 3. In the cervical intraepithelial neoplasia 2 group, visual inspection tests were positive for high-grade squamous intraepithelial lesion in 98.1% of the cases with acetic acid and 94.4% with Lugol’s iodine. Colposcopy identified a probable high-grade squamous intraepithelial lesion in 94.4% of the cases, while cytology only in 42.6%. In the cervical intraepithelial neoplasia 3 group, the visual inspection tests were positive for high-grade squamous intraepithelial lesion in 91.8% of the cases with acetic acid and 95.1% with Lugol’s iodine. Colposcopy identified a probable high-grade squamous intraepithelial lesion in 93.5% of the cases, while cytology in 65.6%. Conclusion: Visual inspection with acetic acid and Lugol’s iodine, and colposcopy test were more accurate for the diagnosis of cervical intraepithelial neoplasia 2 and 3 than through cytopathology.